Passionate leadership : creating a culture of success in every school - Thomas-EL, Salome; Jones, Joseph; Vari, T.J. (United States : Corwin, 2020)
Includes bibliographical references (171-177p.) and index.
300-399
Keywords: Educational leadership; School management and organization; School environment